(3GdJbGHd aj GdbQBf GdcQje (B:s (3OQGSI JMdjdjI ddBjGJ GdeJbGHdI GdYfGUQ (B/s - (3LGHj, eMeO GdCejfs; (3eQcR LeYI GdeGLO ddKbGaI hGdJQGK(B.s (3bSe GdOQGSGJ hGdfTQ hGdTDhf GdNGQLjIs ((3OHj (B- (3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3eQcR LeYI GdeGLO ddKbGaI hGdJQGK,s, 2012)
(3jJfGhd cJGH (B((3GdJbGHd aj GdbQBf GdcQje(B) (3hGdPj bGe HJCdjag eMeO GdCejf LGHj, ehVhY (B((3GdJbGHd(B) (3gPG GdcJGH jYGdL ehVhY (B((3GdJbGHd aj GdbQBf GdcQje(B) (3hgh GdJfGSH Hjf GdYHGQGJ GdbQBfjI Ydi CSGS GdJbGHd Hjf YfGUQgG, eQcRG Ydi GdJMdjd GdgfOSj dgPG GdJbGHd, heG jfTC Yfg ef ObI aj GdfXe, hQhYI aj GdJQcjH, eSJYjfG aj Pdc HGdQShe GdJj JHQR hXjaI gPG GdJdhjf GdHdGZj GdPj hUd Hg GdPcQ GdMcje GdbeI, aCJi efg HGdeCdha ef cdGe GdYQH hZjQ GdeCdha efg, hJhUd Edi HYV GdeHGOF GdegeI GdJj jUdM JWHjbgG Ydi cKjQ ef GdBjGJ(B. s
(3jTJed Ydi cTGaGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B260-263.s
Keywords: (3GdbQBfs -- (3GdHdGZIs